Determinants of Competitiveness of Early-Internationalised Firms - Jarosiński, Mirosław (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The text presents a literature review on the competitiveness of early-internationalized firms (international new ventures, born globals). The competitiveness of enterprises can be tackled in many ways. In relation to early-internationalized firms, the main focus is on their effectiveness and competitive strategies. The analysis of the literature leads to the understanding that the most important determinants are knowledge orientation (possessing, acquiring, processing knowledge and organizational learning) and marketing orientation (very high quality of products, contact with the client, marketing competences). In addition, an important element determining the size of the competitive advantage is local business networks embeddedness.